Taking root in floating cities – space, environment, and immigrant identity in Kerri Sakamoto’s "Floating City" - Antoniak, Joanna (My University, 2020)
Human identity is shaped not only by culture, but also by nature – the environment in which people grow up and live, the places and spaces they visit, work in, and pass on an everyday basis. This people-place bond is particularly important in case of immigrants who are forced to abandon the places they know for a new – and often hostile – environment. This connection between space, environment, and immigrant identity is explored by Kerri Sakamoto, a Japanese-Canadian writer, in her newest novel, Floating City (2018). Focusing on the family narrative of the Hanesakas – and, in particular, the story of Frankie, the oldest son of the family – Sakamoto tells the story of shaping identity through forming a connection with the environment and architecture. The aim of this article is to discuss the way in which Sakamoto presents the people-place bond and its impact on immigrant identity as represented by the connection of the Japanese-Canadians with four elements: water, air, earth, and fire. Furthermore, the article analyses Sakamoto’s version of an alternative history of Toronto and the possible solutions to the current environmental crisis it brings. For this purpose, the author uses a mixture of methodological concepts stemming from postcolonial theory and environmental psychology, such as homing desire, rootlessness, place attachment, non-place, and the people-place bond.
Keywords: Kerri Sakamoto; place attachment; immigrant identity; family narrative